Investigation of the spectrum for the Sturm–Liouville problem with one integral boundary condition - Skučaitė, A.; Skučaitė-Bingelė, K.; Pečiulytė, S.; Štikonas, A. (Nonlinear Analysis: Modelling and Control, 2010)
In this paper, the Sturm–Liouville problem with one classical first type boundary condition and other nonlocal integral boundary conditions of two cases is investigated. We analyze how complex eigenvalues of these problems depend on the parameters of nonlocal integral boundary conditions. Some new results are given on complex spectra of these problems. Many results are presented as graphs of complex characteristic functions.